The influence of emotion dysregulation and perceived social support on the link between childhood emotional abuse and depressive symptoms in college students: a moderated mediation model - Huiyuan Huang; Haiqi Wu; Lin Luo; Bingqing Jiao; Yilin Wu; Guanyang Zou; Jiabao Lin; Wenqi Wang; Lijun Ma (Frontiers in Psychiatry)
BackgroundChildhood emotional abuse is strongly linked to an increased risk of depression. However, the pathways linking the two remain elusive. Our study sought to examine how emotion dysregulation and perceived social support influence the link between childhood emotional abuse and depressive symptoms among Chinese college students.MethodsThis study involved 1728 Chinese college students aged 18-24. We utilized the Emotional Abuse (EA) subscale of the Childhood Trauma Questionnaire, Beck Depression Inventory (BDI), Difficulties in Emotion Regulation Scale (DERS) and Perceived Social Support Scale (PSSS) to assess the interrelationships among the study variables. A moderated mediation model was constructed to elucidate these relationships.ResultsOur results indicated a positive correlation between EA, DERS, and BDI. Conversely, PSSS was negatively correlated with EA, BDI, and DERS. Notably, EA is linked to a heightened vulnerability to BDI, with DERS mediating this association. PSSS moderated both the direct path of EA on BDI and the association between DERS and BDI. Furthermore, gender difference was observed in the role of PSSS. PSSS moderated the link between EA and BDI was significant only in the male group and no longer significant under the condition of high PSSS.ConclusionThis study sheds light on the mediating effect of emotion dysregulation and the moderating effect of perceived social support in the connection between childhood emotional abuse and depressive symptoms. The adverse influence of childhood emotional abuse on subsequent depression may be mitigate through interventions focused on enhancing perceived social support and skills in regulating emotions in college students.